Electrolux : refrigeration and segmentation - Baack, Daniel W., (SAGE knowledge. Cases., 2016)
Electrolux offers a variety of refrigerators and other household goods in many countries all around the world. This case examines Electrolux's marketing practices and product designs across different cultures.